4 - Monnaie, Inflation et Croissance en Côte d'Ivoire - A. Madeleine Niamkey, (Africa Development, 1991)
With the real cash reserves as a factor of production , the Cobb-Douglas production function has been determined in a simultaneous equation model, including an equation to determine inflation, based on A.H. Khan and M. Ahmad methodology. Findings show than an over-increased currency is inflationary ; that real cash reserves are a significant factor of production in the industrial sector of Côte d'Ivoire; and that the level of prices is a source of growth more significant than capital.